Caregiver appraisals of lucid episodes in people with late‐stage Alzheimer's disease or related dementias. Issue 1 (23rd June 2022) - Griffin, Joan M.; Kim, Kyungmin; Gaugler, Joseph E.; Biggar, Virginia S.; Frangiosa, Theresa; Bangerter, Lauren R.; Batthyany, Alexander; Finnie, Dawn M.; Lapid, Maria I.
Abstract: Introduction: Little is known about how family caregivers who witness unexpected and spontaneous communication among people in late stages of Alzheimer's disease and related dementias (ADRD) appraise these episodes of lucidity (EL). Methods: In an electronic, cross‐sectional survey for former and current caregivers who participate in UsAgainstAlzheimer's A‐LIST ®, participants who reported witnessing an EL were asked how positive and stressful ELs were, if they made or changed decisions based on an EL, and what resources they sought out to explain ELs. Results: Caregivers reported 72% of ELs to be quite a bit or very positive, 17% to be stressful, and 10% to be both stressful and positive. Twelve percent of caregivers changed care plans because of ELs and 13% sought out information about ELs. Discussion: These exploratory data suggest caregiver reactions to EL vary. Caregivers may change or postpone care decisions due to EL, and few resources exist to address caregiver queries about EL.